(untitled) (Islas, 2023)
Introduction: This work has the purpose of reviewing the features that make up the phonic identity of Cuban Spanish through the studies carried out in the last decades. Methods: A research based on the historiographic method is carried out, which in turn is supported by the bibliographic-documentary, analysis and synthesis methods as well. Results: The research carried out shows that the most important segmental features are associated with the weakening and allophonic variation of consonants in distended position and between vowels. The intonation studies reveal, in turn, the use of intonation patterns of wide codification in Cuban Spanish and others that show a greater variation, such as the expression of plea and warning. Conclusions: The phonemes /s/ /r/ and /l/ show the highest levels of allophonic creativity in Cuban speech. The neutral patterns of interrogation and enunciation, as well as the expression of astonishment and evidence show a high degree of codification throughout the island.